A Seasonal Analysis of Wind Turbine Characteristics and Wind Power Potential in Manisa, Turkey - Ucar, Aynur; Balo, Figen (Taylor & Francis Inc, 2008)
In this study, wind characteristics and wind energy potential of a site in the western part of Anatolia of Turkey were analyzed using the wind speed data collected during the period 2000 to 2006. The wind speed distribution curves of the investigated location were obtained by using the Weibull and Rayleigh probability density functions based on these data. Monthly mean wind power at the heights 10, 30, 50, and 70m was found. A technical and economic assessment has been made of electricity generation from the wind turbines of capacity 600 kW, 800 kW, 1300 kW, 1500 kW, 2300 kW, and 2500 kW in the investigated site. The yearly energy output and capacity factor produced for the six different turbines were calculated. The capacity factor of wind turbines used in the analysis was found to be between 25 and 34.
Keywords: Wind energy; Weibull and Rayleigh distributions; Wind turbine